PEMBERDAYAAN KELUARGA MELALUI KURSUS PRA NIKAH BERBASIS NILAI-NILAI PENDIDIKAN ISLAM UNTUK MEWUJUDKAN KETAHANAN KELUARGA DI BONDOWOSO, JAWA TIMUR - Matkur; Rahman, Farah Dianita (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2024)
The rising divorce rate and complex family issues in Bondowoso highlight the urgency of comprehensive premarital education. This article examines the implementation of premarital courses based on Islamic educational values as a form of family empowerment to foster family resilience. The community service program was conducted in Bondowoso and Wringin sub-districts, involving 120 participants. The method used included participatory counseling, discussions, and lectures. Key topics covered were Marriage Law, the concept of sakinah family, and reproductive health. The findings indicate high enthusiasm from participants and competent resource persons, although challenges such as time limitations and participant absenteeism were noted. The course effectively instilled Islamic values into family life and strengthened prospective couples' understanding of familial roles and responsibilities. Strengthening the program through extended duration and more comprehensive materials is recommended for future implementation. Peningkatan angka perceraian dan kompleksitas masalah keluarga di Bondowoso menunjukkan pentingnya pembekalan pranikah yang komprehensif. Artikel ini mengkaji pelaksanaan kursus pra nikah berbasis nilai-nilai pendidikan Islam sebagai bentuk pemberdayaan keluarga guna menciptakan ketahanan keluarga. Kegiatan pengabdian masyarakat ini dilaksanakan di Kecamatan Bondowoso dan Kecamatan Wringin dengan melibatkan 120 peserta. Metode yang digunakan adalah penyuluhan partisipatif, diskusi, dan ceramah. Materi yang disampaikan mencakup Undang-Undang Perkawinan, konsep keluarga sakinah, serta kesehatan reproduksi. Hasilnya menunjukkan antusiasme tinggi dari peserta dan narasumber yang kompeten, meskipun terdapat kendala waktu dan ketidakhadiran sebagian peserta. Kursus ini efektif dalam menanamkan nilai-nilai Islam dalam kehidupan berumah tangga dan memperkuat pemahaman calon pengantin terhadap peran dan tanggung jawab keluarga. Diperlukan penguatan pelaksanaan dengan waktu lebih panjang dan dukungan materi yang lebih lengkap.